Involving Knowledge Users in Health Services Research: Collective Reflections and Learning From a National Evaluation of Recurrent Miscarriage Services - Marita Hennessy; Rebecca Dennehy; Hannah O'Leary; Keelin O'Donoghue; RE:CURRENT Research Advisory Group (Health Expectations)
ABSTRACT Introduction Involving knowledge users in research can facilitate the translation of evidence into policy and practice. How to best involve and support various types of knowledge users, including patient and public involvement contributors, in research is an identified knowledge gap. We conducted a national evaluation of recurrent miscarriage care supported by a Research Advisory Group (convened in March 2020) comprising a range of knowledge users, including parent advocates and people involved in the management/provision of services. The Group met virtually nine times, and actively collaborated beyond this on various research activities across the project. In this paper, we share insights from our collective evaluation of these involvement efforts. Methods We drew on records kept over the timespan of the project to describe involvement activities and experiences. Advisory Group members participated in an electronic survey to assess their involvement experiences at two time points (February 2021 and May 2022); we analysed the results descriptively. In May 2022, we hosted a virtual World Café, comprising the Research Team and Advisory Group, to explore what worked well and what could have been improved regarding involvement activities within the project; we analysed this data thematically. Results Responses to both rounds of the survey were positive, with people reporting: their ability to discuss research issues, contribute to the research, express their own views; feeling valued as a partner; that they could bring their own ideas and values to the research; perceived potential to gain status, expertise, or credibility because of their involvement. Themes constructed from the Word Café discussions highlighted that structural and relational spaces shaped the accessibility and experience of involvement. Conclusion Members reported a positive and rewarding experience with a visible impact on the research process but highlighted issues with the feasibility and scope of the research protocol and challenges to autonomous involvement in aspects reliant on clinical expertise. Our analysis reinforces that the relational nature of involvement takes precedence over instrumental aspects or techniques. Realistic study protocols that allow time and space for the evolving nature of research with knowledge users, and institutional and financial support to facilitate meaningful involvement, are needed. Patient or Public Contribution People with lived experience of recurrent miscarriage/pregnancy loss were involved in this evaluation—as members of the RE:CURRENT Research Advisory Group, contributing to the methodology, evaluation activities, interpretation and reporting of findings and insights.